Konstruksi preposisi 'pada' dan kepada 'dalam' ragam bahasa internet: kajian sintaksis berbasis korpus - Faradhiba Salsabila; Susi Yuliawati; Nani Darmayanti (Universitas Mulawarman, 2023)
The use of social media gave rise to internet variety language. This language variety includes low variety language because it is used in informal situations. Preposition ‘pada’ and ‘kepada’ show an interesting linguistic phenomenon in the form of syntactic similarities so that these two prepositions can replace each other in certain situations. The purpose of this study is to analyze the frequency, colligation patterns, and the syntactical roles of prepositions ‘pada’ and ‘kepada’ in internet variety language. This research used AntConc to collect data. This research consists of two stages, namely quantitative and qualitative analysis. Quantitative analysis is used to determine the frequency of preposition ‘pada’ and ‘kepada’ in internet variety language. Qualitative analysis is used to determine colligation patterns and to investigate the syntactical roles of prepositions ‘pada’ and ‘kepada’ in internet variety language. Based on the research result, the frequency of ‘pada’ appears 68 times, while ‘kepada’ appears 53 times. Non-person nominal phrases are the most syntactic categories that follow ‘pada’, while personal nominal phrases are the most syntactic categories that follow ‘kepada’. The preposition ‘pada’ has syntactic roles of time, goal, location, completion, affirm, and recipient. The preposition ‘kepada’ has syntactic roles of target and receiver.